2013
DOI: 10.3319/tao.2012.12.27.01(tt)
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and Anthropogenic Impacts on δ13C Variations in a Stalagmite from Central China

Abstract: In this paper, we present a δ 13 C record that covers the past 750 years at a resolution of 2 -3 years which was preserved in a precisely dated stalagmite (DY-1) obtained from the Dayu Cave on the south flank of the Qinling Mountains in central China. Between 1249 AD and 1800 AD, climate-induced vegetation changes appear to have been the primary control on δ 13 C values at a centennial scale. Variations in precipitation amounts control the residence time of seepage water and may have affected the dissolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…The δ 13 C values 24 are relatively higher during each drought event in the last 500 years too ( Fig. 3 ).…”
Section: Resultsmentioning
confidence: 92%
“…The δ 13 C values 24 are relatively higher during each drought event in the last 500 years too ( Fig. 3 ).…”
Section: Resultsmentioning
confidence: 92%
“…The factors controlling speleothem δ 13 C values have been discussed in many previous studies (McDermott 2004;Fairchild et al 2006;Cosford et al 2009;Li et al 2012;Tan et al 2013). We summarize these factors in the following list.…”
Section: Factors Affecting Speleothem δ 13 C Valuesmentioning
confidence: 96%
“…Previous studies have suggested that vegetation changes above caves (owing to either natural or artificial causes) may influence the carbon isotope compositions (δ 13 C values) of speleothems in the caves (Dorale et al 1998;Hellstrom et al 1998;Genty et al 2001Genty et al , 2003Zhang et al 2004;Baldini et al 2005;Cruz et al 2006;Zhu et al 2006;Fleitmann et al 2009;Frisia et al 2011;Kuo et al 2011;Hartmann et al 2013;Tan et al 2013;Uchida et al 2013;Duan et al 2014). The rationale behind such an interpretation lies in the fact that carbon isotope composition in speleothem derives from soil CO2 dissolved in the drip water, and the soil CO2 is produced by plant respiration and organic matter decomposition.…”
mentioning
confidence: 99%
“…If the climatic deterioration was responsible for the obvious isotopic shift in Shihua cave records, it should also be observed in Zhenzhu cave record, given the coherence between them before this period (Figures 5 and 6). Various anthropogenic impacts on the variations of stalagmite δ 13 C have been widely reported in previous studies (Hartmann et al, 2013;Hou et al, 2003;Kuo et al, 2011;Li et al, 1998;Tan et al, 2013Tan et al, , 2020Zhang et al, 2015). For instance, a prominent enrichment in δ 13 C values of an Indonesian stalagmite between ∼1.1 and ∼0.5 ka BP has been attributed to deforestation and cultivation (Hartmann et al, 2013).…”
Section: Imprints Of Climate and Human Activity On Isotopic Variabili...mentioning
confidence: 81%
“…Carbon isotope compositions of speleothems mainly reflect that of soil CO 2 overlying the cave (Genty & Massault, 1999;Genty et al, 2001;Li et al, 2011;Luo & Wang, 2009), which are influenced by biological processes such as plant root respiration, organic matter decomposition, and vegetation type (C4/C3 plant ratio) (Baker et al, 1997;Denniston et al, 2001;Dreybrodt, 1980;Duan et al, 2014Duan et al, , 2022Genty et al, 2003Genty et al, , 2006Hou et al, 2003;Jia et al, 2022;McDermott, 2004;Tan et al, 2013;Yin et al, 2017;Zhang et al, 2021;Zhao et al, 2020). Before 1588 AD, the δ 13 C of both stalagmites TS9701 and TS950 fluctuates between −11.7‰ and −7.7‰ (Figure 2), indicating that the vegetation overlying Shihua cave was predominantly C3 plants, as expected from speleothem δ 13 C values (−14‰ to −6‰) at such sites (Baker et al, 1997;Dreybrodt, 1980;McDermott, 2004).…”
Section: Imprints Of Climate and Human Activity On Isotopic Variabili...mentioning
confidence: 99%